An architecture for centralized SIP-based audio conferencing using application layer multicast - Simões, J.; Costa, R.; Nunes, P.; Lopes, R.; Mathy, L. (PGNet 2006 - The 7th Annual PostGraduate Symposium on The Convergence of Telecommunications, Networking and Broadcasting, 2006)
Audio conferencing is an important aspect of Internet Telephony services. In this article, using a centralized conferencing architecture, we propose to employ application layer multicast for media distribution, by using “agents” responsible for the delivery of streaming media to end-clients, aiming at reducing the traffic in the network and the server workload. In this model, we use the concepts of active client, which exchanges media directly with the server, and passive client, which is limited to receive media from its agent. In our implementation we use the Real Time Protocol (RTP) for data transmission and the Session Initiation Protocol (SIP) for signaling, hence making it compatible with most existing state-of- the-art hardware and software.